1999
DOI: 10.1006/dbio.1999.9254
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofXenopusRalB and Its Involvement in F-Actin Control during Early Development

Abstract: We describe the characterization and a functional analysis in Xenopus development of RalB, a small G protein. RalB RNA and protein are detectable during oogenesis and early development, but the gene is expressed only weakly in adult tissues. The RalB transcripts are processed by poly(A) extension during oocyte maturation and up to the gastrulation stage. Microinjection of wild-type or mutant RalB RNAs was performed in fertilized eggs in order to gain insight into the function of RalB during development. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Ral proteins are activated by the Ras effector, Ral-GDS (Kikuchi et al, 1994;Wolthuis et al, 1998b) and have been directly implicated in various cellular mechanisms, such as endocytosis (Nakashima et al, 1999) and regulation of the actin cytoskeleton (Ohta et al, 1999). By microinjecting different mutant forms of XralB into Xenopus embryos, we have shown that expression of an inactivate form of XralB, XralB S28N, leads to abnormal gastrulation movements, whereas a constitutively active form, XralB G23V, causes disruption of the actin cytoskeleton (Moreau et al, 1999).…”
Section: Of Particular Interest Is Whether or Not Ras Directly Influementioning
confidence: 99%
See 3 more Smart Citations
“…Ral proteins are activated by the Ras effector, Ral-GDS (Kikuchi et al, 1994;Wolthuis et al, 1998b) and have been directly implicated in various cellular mechanisms, such as endocytosis (Nakashima et al, 1999) and regulation of the actin cytoskeleton (Ohta et al, 1999). By microinjecting different mutant forms of XralB into Xenopus embryos, we have shown that expression of an inactivate form of XralB, XralB S28N, leads to abnormal gastrulation movements, whereas a constitutively active form, XralB G23V, causes disruption of the actin cytoskeleton (Moreau et al, 1999).…”
Section: Of Particular Interest Is Whether or Not Ras Directly Influementioning
confidence: 99%
“…cellular morphology via modulation of the cytoskeleton. In previous studies, we have characterised XralB, a small G protein of the Ras family, isolated by differential screening of a subtractive cDNA library (Moreau et al, 1999). This protein cycles between an inactive GDP-bound and an active GTPbound conformation.…”
Section: Of Particular Interest Is Whether or Not Ras Directly Influementioning
confidence: 99%
See 2 more Smart Citations
“…In Xenopus oocytes and eggs, pigment granule localization is controlled by actin fibers (Palecek et al, 1978;Campa et al, 1993;Boyle et al, 2001). However, actin fiber disruption is probably incompatible with normal development (Moreau et al, 1999). Hence, we believe that the XDel1-D2 protein displaces the pigment granules from their normal anchorage site.…”
Section: Pigment Granule Translocationmentioning
confidence: 89%